Number And Set Theory in Gamelan: An Ethnomathematics Study - Oktaviyani, Dewi Mekarsari; Utami, Niken Wahyu; Utama, Gusnandar Yoga (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2023)
Numbers and Sets are mathematical subject matter that can be learned using context in life. One of the contexts that can be used is gamelan artifacts. Gamelan contains the values of local wisdom that have become part of the identity of the Indonesian nation. Ethnomathematics sets and numbers in gamelan must be explored as contexts in related mathematical learning. The study aims to explore ethnomathematics related to the sociocultural context of Gamelan, offering an alternative approach to mathematical learning on sets and numbers. Employing an interpretive ethnographic approach based on Alangui's framework, the study unfolds across two art studios and three schools in Indonesia, engaging karawitan art culturalists and junior high school mathematics teachers as key informants. Through observation, documentation, field notes, and interviews, our findings reveal that gamelan artifacts can enrich the teaching of sets and numbers with their various types, shapes, and sizes. Hence, the results offer a transformative perspective for teachers, preservice teachers, and mathematics educators to integrate gamelan artifacts into mathematics lessons.